Ionic Modulation of Electrical Conductivity of ZnO Due to Ambient Moisture. Issue 17 (9th July 2019) - Milano, Gianluca; Luebben, Michael; Laurenti, Marco; Porro, Samuele; Bejtka, Katarzyna; Bianco, Stefano; Breuer, Uwe; Boarino, Luca; Valov, Ilia; Ricciardi, Carlo
Abstract: Moisture can strongly affect reliability and functionalities of a wide range of electronic devices based on metal‐oxide semiconductors, where the electrical conductivity can be influenced by the deposition technique and the environment. In this work, the influence of moisture on electrical conductivity of zinc oxide (ZnO) is investigated, revealing that moisture and protons can impact not only the electronic conduction, but can provide additional ionic species that actively participate in the conduction mechanism. Single crystalline nanowires are exploited as model systems for investigating the effect of adsorbed species on ZnO surfaces, revealing that hydroxide species are responsible for the creation of a depletion region on the surface that decreases the electronic conductivity. The same mechanism is attributed to the decreasing of conductivity by increasing the moisture content in ZnO polycrystalline films, where moisture is adsorbed at grain boundaries. At high activities of moisture, it is observed that moisture‐related species can migrate along the highly oriented grain boundaries resulting in an increase of the global conductivity due to the ionic current flowing in parallel to the electronic one. More generally, the results highlight the importance of the environment and the ionic contribution in determining the electrical conductivity of nanostructured devices. Abstract : In this work, the influence of moisture on electrical conductivity of ZnO is reported. It is shown that adsorbed water‐related species can not only impact the electronic conduction mechanism by creating a depletion region on the ZnO surface but can also provide additional ionic species responsible for the formation of an ionic conduction channel in parallel to the electronic one.